2018
DOI: 10.2337/db18-0638
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Improves Insulin Sensitivity and Suppresses Gluconeogenesis via the Transcription Factor Foxo1

Abstract: Premenopausal women exhibit enhanced insulin sensitivity and reduced incidence of type 2 diabetes (T2D) compared with age-matched men, but this advantage disappears after menopause with disrupted glucose homeostasis, in part owing to a reduction in circulating 17b-estradiol (E 2 ). Fasting hyperglycemia is a hallmark of T2D derived largely from dysregulation of hepatic glucose production (HGP), in which Foxo1 plays a central role in the regulation of gluconeogenesis. Here, we investigated the action of E 2 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
151
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(162 citation statements)
references
References 65 publications
7
151
1
3
Order By: Relevance
“…As alluded to previously, evidence in the literature indicates the binding affinity of 17β-E2 for ERs is dramatically greater than 17α-E2, which has been confirmed with competitive binding assays [32][33][34][35]. In males, very few studies have evaluated the role of ERα in metabolism, although a few recent reports have suggested that ERα plays tissue-specific roles, particularly in the liver, by regulating male metabolic homeostasis [38][39][40][41]55]. These studies, coupled with our current findings, led us to speculate that 17α-E2 may be signaling through ERα in the liver to reverse metabolic disease and potentially extend healthspan and/or lifespan in males.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As alluded to previously, evidence in the literature indicates the binding affinity of 17β-E2 for ERs is dramatically greater than 17α-E2, which has been confirmed with competitive binding assays [32][33][34][35]. In males, very few studies have evaluated the role of ERα in metabolism, although a few recent reports have suggested that ERα plays tissue-specific roles, particularly in the liver, by regulating male metabolic homeostasis [38][39][40][41]55]. These studies, coupled with our current findings, led us to speculate that 17α-E2 may be signaling through ERα in the liver to reverse metabolic disease and potentially extend healthspan and/or lifespan in males.…”
Section: Discussionmentioning
confidence: 53%
“…For instance, Allard and colleagues recently demonstrated that genomic actions of ERα regulate systemic glucose homeostasis in mice of both sexes and insulin production and release in males [38]. Other studies have also determined that hepatic steatosis and insulin sensitivity, and therefore the control of gluconeogenesis, are regulated through FOXO1 in an ERα-dependent manner in male mice [39]. Furthermore, liver-specific deletion of ERα was sufficient to abrogate similar estrogen-mediated metabolic benefits [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…improves insulin sensitivity and suppresses hepatic gluconeogenesis through inhibition of Foxo1 via activation of ERα-PI3K-Akt signaling by investigating the action of E2 on glucose homeostasis in male and ovariectomized female control and liver-speci c Foxo1 knockout mice 27 . It was reported that estrogen receptor a (ERa) regulated β-cell formation during pancreatic development 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Research on ER-positive breast cancer (cell line MCF-7 xenografts) demonstrated that tamoxifen, a selective ER modulator, effectively inhibits classical ER-dependent transcription, including the transcription of IGF1R gene product [92]. In vivo studies have shown that E2 improves insulin sensitivity and glucose tolerance via activation of ERα/PI3K/Akt signaling [93,94]. However, E2 has been demonstrated to inhibit the in vitro binding of insulin to INSR by binding to both insulin and its receptor instead, an observation strongly suggesting the ability of E2 to induce IR either directly or indirectly [95].…”
Section: Estrogensmentioning
confidence: 99%